The Effect of Fundamental Factors and Systematic Risk on the Return of LQ45 Shares Listed on the Indonesia Stock Exchange - Rully Setyo Wibowo; Agus Rahman Alamsyah; Ike Kusdyah Rachmawati (Quantitative Economics and Management Studies, 2023)
This study aims to find out the influence of fundamental factors which are represented by the Current Ratio, Total Asset Turn Over, Debt to Equity Ratio, Return On Equity and Price Book Value and Systematic Risk which is represented by beta toward stock returns of LQ45 stock that listed in Indonesia Stock Exchange period 2018 - 2021. Purposive sampling is used as the sampling technique with criteria: The stock of industry in LQ45 has always seen the annual financial report over the period 2018-2021 and could be made financial ratio from the annual report as used in this research. 28 samples of LQ45 stock were taken in this research. The partial regression coefficient was tested using multiple linear regression and hypothesis testing using the statistical t-test with a level of significance of 5%. The classic assumption test, which also included the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test, was also run. Based on the result of this research, classic assumption deviation has not founded, this indicated that available data has fulfilled the condition to use a multiple regression model. Empirical evidence of analysis showed as partially Price to Book Value and Systematic Risk have a positive dan significant effect on stock return, while CR, TATO, and DER have no significant effect on stock returns and ROE has a negative and significant effect on LQ45 stock returns for the 2018-2021 period. The result of this research indicated that PBV and Systematic Risk were used by the investor to predict the stock return of LQ45 company period 2018-2021.